Online Customers Review and Buying Behaviour among Students at Heritage Polytechnic, Nigeria - Nwokeocha, Ifeanyi Martins (Devotion : Journal of Research and Community Service, 2025)
In the 21st century, the Internet has revolutionized advertising by providing businesses large and small alike unprecedented access to global audiences at lower costs and faster rates. However, this shift has also diminished advertisers’ monopoly over information, giving rise to a consumer-centric economy where users actively engage in evaluating and discussing product experiences online. This study aims to examine how online product reviews influence consumer perception and buying behavior. Employing a survey research design, data were collected through electronic questionnaires from a sample of 333 respondents, determined according to Phillip Meyer’s sampling recommendation. The results reveal that continuous online discussions and reviews significantly affect consumers’ purchasing decisions, as they tend to rely heavily on peer opinions before making a purchase. Negative reviews were found to reduce purchase intention, while positive feedback strengthened brand trust and loyalty. The study concludes that online product reviews play a crucial role in shaping consumer behavior in the digital marketplace. It implies that advertisers and product manufacturers must actively monitor, respond to, and integrate consumer feedback into product improvement strategies to foster positive perceptions and sustain competitiveness in an increasingly transparent digital environment.